Violence within the family and its impact on the delinquency of children: (Field research at the boys' rehabilitation school model) - Hamid Atiyah, Jameel (Al-Adab Journal, 2019)
Objective of the research: To detect the impact of domestic violence in juvenile delinquency in society.Family violence is a fundamental variable in juvenile delinquency when some families practice different types of violence against their children and children in a way that is incompatible with modern methods of education, influenced by rigid parenting methods, the result of dominant patriarchal culture, whether through tribal values Or paternal authority in the popular areas of the cities, would take him from the authority of the Father and his gentleness in pedagogy. Therefore, the injustice is on the children of adolescents in captivity, and there is no doubt that the severe psychological pressures have a negative impact on the behavior of children, which leads to their rebellion and delinquency and then put them in error which makes them closer to deviant behavior and commit acts contrary to the values ​​of society, so the importance of research stands out in showing the impact Domestic violence and juvenile delinquency.A study was conducted on the juvenile rehabilitation school in the Ministry of Labor and Social Affairs, where a study was conducted on all juvenile delinquents of (100) boys using the comprehensive survey methodology and organizing a questionnaire I ask about the subject divided into two parts: The research used the interview, observation and questionnaire as basic tools for all research data.